The Evolving character of conflict: Implications for United Nations peacekeeping - Deb, Alok (U.S.I. Journal)
This article explores the evolving characters of conflict and it's implications for United Nations (UN) Peacekeeping in an era marketed by technological advancements and shifting geopolitical dynamics. Modern conflicts, such as the Ukraine-Russia war and maritime disputes in the South China Sea, demonstrate the increasing use of drones, artificial intelligence, and hybrid warfare tactics, involving state and non-state actors across multiple domains. Traditional drivers of conflict-geopolitical rivalries, resource competition, and socio- economic disparities-persist while emerging threats, such as transnational crime and technological coercion, reshape the nature of warfare. This article emphasises the need for the UN to rethink peacekeeping doctrines, mandates and capabilities. Clear mandates, modular mission structures, and specialised personnel equipped to counter cyber threats and drones are essential. By incorporating new conflict management approaches, such as mediation and multi-domain strategies, this article highlights how the UN can adapt it's peacekeeping framework to sustain international peace and security in a volatile world.
Keywords: United Nation (UN), UN Peacekeeping, Ukraine-Russia war, South China Sea, Cyber threats, International peace